Microstructural changes in the thalamus after mild traumatic brain injury: A longitudinal diffusion and mean kurtosis tensor MRI study. (28th January 2017) - Næss-Schmidt, Erhard Trillingsgaard; Blicher, Jakob Udby; Eskildsen, Simon Fristed; Tietze, Anna; Hansen, Brian; Stubbs, Peter William; Jespersen, Sune; Østergaard, Leif; Nielsen, Jørgen Feldbæk
Abstract: Primary objective : The primary aim of this study was to assess microstructural changes in the thalamus, hippocampus and corpus callosum with a fast mean kurtosis tensor (MKT) technique, in the acute and sub-acute phase after mTBI. It was hypothesized that MKT would differ between baseline and follow-up in patients. The secondary aim was to relate diffusion measures to symptoms of mTBI. Research design : A longitudinal case-control study. Methods and procedures : Twenty-seven patients with mTBI and 27 age- and gender-matched healthy controls were enrolled in the study. Patients were scanned within 2 weeks and 3 months after mTBI, while the controls were scanned once. Main outcomes and results : MKT decreased significantly ( p = 0.02) from baseline to follow-up in the thalamus in patients. Compared to healthy subjects, thalamic MKT values were significantly larger in patients at baseline ( p = 0.048). Secondary analysis revealed a significant decrease ( p = 0.01) in fractional anisotropy in the splenium of corpus callosum from baseline to follow-up. Conclusions : The current study indicates microstructural changes in the thalamus and corpus callosum from within 14 days to 3 months after mTBI and suggests MKT as a potential biomarker after mTBI.